Penetapan Harga Menurut Ibnu Taimiyah - St. Fatima; Soumena, Moh. Yasin; St. Nurhayati; Ikhsan Gasali; A. Rio Makkulau (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
Pricing is an important phenomenon that needs to be studied in more depth. Prices always change from time to time depending on what is influencing them at that time. Changes in demand and supply are things that greatly influence price increases or decreases. Prices in Islamic economics are influenced by market conditions in the sense that they depend on the level of demand and supply. Ibn Taimiyah expressed the view that if prices flow naturally according to market conditions, fair prices will emerge so that the government is not allowed to interfere in setting them. The type of research used in this research is library research. This research was carried out based on library data, by analyzing the thoughts of the figure Ibn Taymiyah regarding the basis of price setting, as well as books, journals and scientific works related to the research focus. This research is expected to develop the study of Sharia Economic theory, especially Ibn Taymiyah's perspective price theory. It is also hoped that this research will facilitate people's understanding of Ibn Taimiyah's perspective price theory and can provide them with considerations in the economic decision-making process. The results of the research show that in setting prices there are several indicators used by Ibn Taymiyah, as follows: There is a standard price, Products being traded can be accepted for the same thing, Specific time, There is no element of fraud.